(untitled) (Plant Tissue Culture and Biotechnology, 2020)
Indirect regeneration of plantlets from multiple shoot induction of Corallocarpus epigaeus was obtained from leaf and nodal explants on MS with different concentrations of BAP in combination with IAA/IBA or IBA alone. Among all the combinations, BAP and IBA exhibited maximum regeneration. High frequency of multiple shoots (89%) was obtained on BAP (2.0 mg/l) and IBA (1.5 mg/l) in nodal explants. Maximum mean shoot length of 6.8 ± 0.33 cm was obtained in nodal explants cultured on BAP (1.0 mg/l) + IBA (0.5 mg/l), followed by leaf explants with 6.7 ± 0.47 cm on BAP (3.0 mg/l) + IAA (2.5 mg/l). The highest frequency of rooting (88.3%) was obtained on NAA (1.0 mg/l) and IBA (2.0 mg/l) with 21.83 ± 0.57 mean number of roots. The well-rooted healthy plantlets were acclimatized with a survival rate of 80%. Inter simple sequence repeat (ISSR) analysis revealed the genetic similarity of in vitro raised plants with the mother plant. Plant Tissue Cult. & Biotech. 30(2): 219-229, 2020 (December)